Second Language Acquisition And Linguistic Freedom Through Drama - Peter E. R. Jordan (University of Kuningan, 2015)
The important part played by drama in second language acquisition has long been appreciated. An active and inter-active teaching environment facilitates learning in a number of ways, by motivating and sustaining attention, as well as offering a secure environment for experimentation. Drama offers students a pro-active approach to learning, promoting a collective feeling of being in a shared enterprise. This paper discusses how drama can make a significant contribution to second language acquisition. In particular, I focus on the techniques of the Italian Commedia dell’Arte, the first truly professional theatre form to emerge in Europe in the mid-sixteenth century. Its core elements of improvisation and mask are highly effective tools in language learning, empowering students and allowing them to take ownership of the unfamiliar. Improvisation provides a dramatically engaging forum for experimentation that can help to overcome cognitive blocks and prioritise communication as the ultimate imperative. Masks which leave the mouth free for speech can help students overcome the natural inhibitions that often come with attempts to express oneself in an unfamiliar linguistic code.Keywords: language acquisition, drama, improvisation, mask